LAW COLLEGE LIBRARIES’ BEST PRACTICES TO ENCOURAGE USAGE OF LIBRARY: OFFLINE & ONLINE SERVICES - Jaytakar, Sarika Tushar; Pal, Asharam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Purpose Best practices help to improve the quality of library services. Librarians can actively engage in these best practices, connect with their groups, attract more library readers/ visitors, and fruitfully recommend their resources and services. These library services and innovative practices can help to get a good score in the NAAC (National Assessment and Accreditation Council). The significance of library best practices is to boost readers’ research needs. It can help the librarian understand how to develop library services to encourage library book reading. Design/methodology/approach The research adopts an empirical study. This research investigates the best practices functional in academic law libraries. Such practices for physical and online library services encourage users to explore the library. Implementation of these strategies assists librarians in achieving favourable outcomes in NAAC accreditation. Findings The study will examine how libraries’ innovative practices enhance accreditation standards and identify areas where improvements are needed. Best practices reduce the gap between readers and the library’s collection and create awareness about available resources, including e-resources. This study contributes to raising awareness among library administrators and staff about various library services to enhance online and offline library usage. Best practices also help to improve the skills of library staff. As per the findings, the librarian has to promote library services. Research limitations The limitation of this study is that it is for law colleges affiliated with the University of Mumbai. The population of this study covers all law college librarians and library staff affiliated with the University of Mumbai. Though the total number of law colleges is 84, only 61 staff members responded to the questionnaire used for the empirical study. Practical implications The findings of the study contribute to enhancing the NAAC score. With the help of this study, library staff and those in charge of the library can show their capabilities in implementing innovative best practices in the library. This study helps to 1. Start various innovative library services to enhance library usage. 2. To create awareness among law colleges about the library’s best practices for the NAAC grading. Originality/value This study is among the few papers in the library science literature on best practices applied in law college libraries. It increases our understanding of best practices in libraries.